PROBLEMATIKA SISWA PADA QIRĀ’AH JAHRIYYAH TEKS BAHASA ARAB SERTA UPAYA PERBAIKANNYA DI SMK YAPARI AKTRIPA BANDUNG - Andriani, Nia (Departemen Pendidikan Bahasa Arab, 2018)
This study aims to describe the difficulties of students in QirÄâ€™ah jahriyyah and their improvement efforts. This research uses a qualitative approach with descriptive methods. Participants in this study were grade X students in Hospitality 2 Accommodation and grade x Arabic language teachers. Data collection techniques used were observation, interviews, documentation and tests. The results showed that the difficulty of pronouncing hijaiyyah letters based on Makhorijul letters experienced by grade X students of hospitality accommodation at Yapari Vocational High School Bandung was located in the Makhraj letters of Al Jauf (oral cavity), namely in the long vowel sounds, Al-Halq (throat) namely the sound of letters Ø¹ and Ø®, and Al-Oral (tongue), namely the sound of the letters Ø´ - Ø¶ - Øµ - Ø« - Ø°. One of the efforts to help improve the quality of student reading is by training and accustoming students to read as much and as often as possible in various opportunities both in the form of school programs and subject teacher programs.